2019
DOI: 10.2478/scjme-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

HVAC Systems Heat Recovery with Multi-Layered Oscillating Heat Pipes

Abstract: The aim of this work is to investigate a heat performance of a Multi-Layered Oscillating Heat Pipes Heat Exchanger (ML-OHPHE) for the application of heat recovery in heating, ventilation and air conditioning systems (HVAC systems). The heat exchanger is investigated experimentally under different conditions of heat loads and filling ratios. The experimental data results are compared to the data obtained from Honeywell’s UniSim® Design Suite software. In the end the NTU analysis of the ML-OHPHE is done and a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Experimental tests under different conditions were conducted and compared with simulations using Honeywell's UniSim ® Design Suite software. The results suggest that the ML-OHPHE could effectively serve as a passive heat transfer device for HVAC heat recovery [40].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Experimental tests under different conditions were conducted and compared with simulations using Honeywell's UniSim ® Design Suite software. The results suggest that the ML-OHPHE could effectively serve as a passive heat transfer device for HVAC heat recovery [40].…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies explore the heat performance of a Multi-Layered Oscillating Heat Pipe Heat Exchanger (ML-OHPHE) for heat recovery in HVAC systems [40]. Experimental tests under different conditions were conducted and compared with simulations using Honeywell's UniSim ® Design Suite software.…”
Section: Introductionmentioning
confidence: 99%
“…Kapilan et.al [14] performed a CFD analysis is used to analyse the evaporative cooling system in a refrigerator and air-conditioning system. KABÁT Juraj et.al [15] performed an experiment on heating, ventilation and air conditioning systems and conclude that the onset of stable oscillations of the working fluid heavily increases the heat transfer performance compared to the empty heat exchanger.so heat exchanger also plays an important role in improving the performance of a refrigeration system.…”
Section: Introductionmentioning
confidence: 99%
“…Jouhara and Althoughmmon shown that employing heat pipe-based free cooling systems in HVAC systems could result in potential energy savings of up to 75% [2,3]. Kabat, Guzela, and Peciar, get the best heat exchanger performance from the heat pipe at a 50% fill ratio [4].…”
mentioning
confidence: 99%